The Use of Index Numbers in Demand Analysis - Bergstrom, A. R. (Review of Economic Studies, 1955)
Journal Article The Use of Index Numbers in Demand Analysis Get access A. R. Bergstrom A. R. Bergstrom Auckland, N.Z. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 17–26, https://doi.org/10.2307/2296147 Published: 01 April 1955